DESAIN E-VOTING PILKADA KOTA BOGOR MENGGUNAKAN PROTOKOL TWO CENTRAL FACILITIES YANG DIMODIFIKASI - Kusumah, Fitrah Satrya Fajar; Guritman, Sugi; Giri, Endang Purnama (Krea-TIF: Jurnal Teknik Informatika, 2015)
One of Indonesian election isthe local elections for regional head thatare still using conventional election type.The conventional election type stillspend a lot of time and prone of mistakesmade by humans, including fraudscommitted by certain parties. Thisresearch is based on two centralfacilities protocol in Schneier book(1996) and a continuation of previousresearch by Sireesha and Chakchai(2005) which has developed a secureelection with two central facilitiesprotocol that implement the developmentof Central Legitimization Agency (CLA)and the Central Tabulating Facilities(CTF) to create a secure virtualelections and Wardhani (2009) whichimplement the protocol Two centralfacilities at IPB online voting. Thisresearch collaboration with the KPUBogor and Bogor Information andCommunications, for the purposes ofanalyzing and studying the variouselections policy of regional heads ofBogor. Through this study found adesign system using a protocol e-votingTwo central facilities modified.However, this design is still requirefurther research to be applicable forBogor Regional Head election.